2021
DOI: 10.3390/plants10020388
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foliar Application of Chitosan Dissolved in Different Organic Acids on Isozymes, Protein Patterns and Physio-Biochemical Characteristics of Tomato Grown under Salinity Stress

Abstract: In this study, the anti-stress capabilities of the foliar application of chitosan, dissolved in four different organic acids (acetic acid, ascorbic acid, citric acid and malic acid) have been investigated on tomato (Solanum lycopersicum L.) plants under salinity stress (100 mM NaCl). Morphological traits, photosynthetic pigments, osmolytes, secondary metabolites, oxidative stress, minerals, antioxidant enzymes activity, isozymes and protein patterns were tested for potential tolerance of tomato plants growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 101 publications
(81 reference statements)
6
34
0
Order By: Relevance
“…Hycorn-11, respectively, which are two Z. mays cultivars, at 160 mM NaCl stress and concluded that the P1574 cultivar is more salt-tolerant than the Hycorn-11 cultivar. Similarly, upon exposure to 100 mM NaCl, total phenols (by 60%) and AsA (by 55%) were increased in S. lycopersicum plants together with enhanced SOD, CAT, POD and PPO activities [130]. Jiang et al [131] highlighted the TaSOS1 gene in response to salt stress in two spring T. aestivum genotypes, Seri M82 (salt-sensitive) and CIGM90.863 (salt-tolerant), and observed a higher expression of most of the 18 TaSOS1 genes in the roots of salt-tolerant seedlings than the salt-sensitive seedlings.…”
Section: Antioxidant Defense System In Plants Under Salinitymentioning
confidence: 97%
“…Hycorn-11, respectively, which are two Z. mays cultivars, at 160 mM NaCl stress and concluded that the P1574 cultivar is more salt-tolerant than the Hycorn-11 cultivar. Similarly, upon exposure to 100 mM NaCl, total phenols (by 60%) and AsA (by 55%) were increased in S. lycopersicum plants together with enhanced SOD, CAT, POD and PPO activities [130]. Jiang et al [131] highlighted the TaSOS1 gene in response to salt stress in two spring T. aestivum genotypes, Seri M82 (salt-sensitive) and CIGM90.863 (salt-tolerant), and observed a higher expression of most of the 18 TaSOS1 genes in the roots of salt-tolerant seedlings than the salt-sensitive seedlings.…”
Section: Antioxidant Defense System In Plants Under Salinitymentioning
confidence: 97%
“…Plant biostimulants include diverse substances that enhance plant growth through the stimulation of natural processes such as nutrient uptake efficiency, and tolerance to abiotic stress conditions [25,26]. It has been reported that the application of natural biostimulants, such as plant extracts enriched with key biostimulants, can improve plant growth under stress conditions more than that by synthetic chemicals [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…To cope with drought tolerance, several reports published in past decades on the application of NPs such as TiO 2 application in Linum usitatissimum via elevating pigmentation and reducing the activity of Malondialdehyde (MDA) and Hydrogen peroxide (H 2 O 2 ) [ 119 ], ZnO promotes effective seed germination in Glycine max [ 120 ], CuNPs improve pigmentation, biomass and grain yield in Z. mays [ 121 ]. In case of salinity stress, seed soaking, nutrient solutions, and seed priming methods are used for evaluation in G. max, S. lycopersicum, and Gossypium hirsutum respectively [ 122 124 ].…”
Section: Nanoformulations As a Promising Tool In An Agricultural Systemmentioning
confidence: 99%